Steady Progress and Significant Challenges in the Field of Tumor and Cancer Research in Bangladesh: An Overview - Giasuddin, Abu Sayed Mohammad; Rokonuzzamman, Sarder Mohammad; Jalaluddin, Mohammad; Banu, Laila Arjumand (British Journal of Healthcare and Medical Research, 2025)
Tumor and cancer research in Bangladesh is an evolving field with both steady progresses recently and significant challenges. The 2013 Series Bangladesh: Innovation for Universal Health Coverage, published in The Lancet, reported on Bangladesh’s health achievements and challenges particularly on exceptional health advances at low cost than other countries in Asia. Additionally, several national and subnational studies have reported the burden of different diseases and risk factors in Bangladesh at different points during the past three decades i.e. from 1990 to 2019 in Bangladesh. Cancer is a leading cause of death of children and adolescent worldwide and it represents one of the most significant public health problem and challenges of the century with a particularly devastating impact on developing nations. Several studies have been reported evaluating qualitatively and quantitively documenting research progress on tumors and cancers situation from Bangladesh. In the present article, we have made an overview of this field with background to burden of diseases and risk factors, some reported studies from Bangladesh on tumors and cancers and steady research progress on tumors and cancers and significant challenges to it in Bangladesh. Further continued research affords along these fronts are therefore warranted and vitally important.